Optimization of the "Loose Tea Blooming" Process for Guizhou Green Tea and Analysis of Characteristic Volatile Compounds - Linyao SONG; Hui XU; Siyao WU; Fengwei MA; Qiang FEI; Junyi DENG; Dajuan SHI; Yuze LIU; Yichen ZHAO; Xuan DONG; Su XU (Shipin gongye ke-ji)
The organic green tea sourced from Weng'an County in Guizhou Province, which meets EU standards, was utilized as the raw material for producing fermented tea through the solid-state fermentation of Eurotium cristatum. The optimization process for the fermented tea was also conducted. Concurrently, volatile compounds in both the raw material and the final product were detected using headspace solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS), followed by an analysis of the characteristic volatile compounds. The sensory quality and functional indicators, including water extracts, tea polyphenols and free amino acids of the fermented tea, were combined to form comprehensive evaluation indices. The optimal preparation conditions for fermented tea were determined through single factor tests and response surface analysis, with the identified processing conditions being temperature at 28 ℃, water content at 40%, inoculation amount at 1‰, and fermentation time at 8 days. The final fermented tea exhibited a mellow taste, bright orange and yellow color, pure aroma, and achieved a comprehensive score of 83.75±2.52. Furthermore, 18 characteristic volatile compounds with OAV>1 were identified in both green tea and the final fermented tea, revealing a strong "golden flower" aroma in the fermented tea, attributed to eight volatile compounds like linalool and methyl salicylate. Physicochemical analysis of the final fermented tea indicated moisture content of 3.9%±0.47%, ash content of 5.92%±0.21%, and water extract content of 43.92%±0.07%, all surpassing the Chinese national standard for Fu Brick Tea (GB/T 32719.5-2018 Dark tea-Part5: Fu tea). This research serves as a theoretical reference for the preparation of fermented tea using the "loose tea blooming" method.